BRAND EQUITY ON CONSUMER PURCHASING DECISIONS - Roby Ahada; Irsyad Dhahri; Iyad Abdallah Al- Shreifeen (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to examine the effect of brand equity on consumer purchasing decisions, focusing on various dimensions such as brand awareness, perceived quality, and brand loyalty in the context of consumer behavior. The research method carried out in this study uses the literature research method. The results showed that brand equity has a significant and positive influence on consumer purchasing decisions. Brand awareness proved to be a crucial starting point in the purchase decision process, attracting consumers' attention and making them more open to information about the product or service. Perceived quality was found to be an important factor influencing consumer expectations and satisfaction, which in turn influences purchasing decisions. Brand loyalty is reinforced by consistent positive experiences, contributing to repeat purchases and word-of-mouth recommendations, which increase the long-term value of the brand in a competitive market. The findings of this study underscore that brand equity is a critical element that shapes and influences consumer purchasing decisions. Investments in brand equity strategies that focus on building awareness, maintaining positive quality perceptions, and increasing consumer loyalty can help companies not only in attracting new customers but also in retaining existing customer groups. Therefore, strategic management of the elements of brand equity is the key to improving the competitiveness and sustainability of the company in a dynamic market.